The Impact of Iraqi Politicians' Use of Twitter on Public Political Awareness - Najm, Turki Hasan; Yusuf, Leith Bader (ALBAHITH ALALAMI, 2023)
This research investigates the impact of Iraqi politicians' utilization of Twitter as an interactive media tool to communicate their positions and perspectives on political events. Twitter has become a significant platform for dialogue and interactive discussions. The survey method, specifically the descriptive approach, was employed to answer research questions and achieve objectives. A sample of 100 Iraqi Twitter users was selected, considering demographic variables such as gender, age, and educational background, during the period from September 15 to October 1, 2022.